2017
DOI: 10.17159/sajs.2017/20160384
|View full text |Cite
|
Sign up to set email alerts
|

Growth of soil algae and cyanobacteria on gold mine tailings material

Abstract: The goal of revegetation of gold mine tailings storage facilities is to reduce aeolian pollution, nutrient leaching and erosion caused by exposure to wind and water. The establishment of biological soil crusts may prove to be a more cost-effective way to reach the same goal and the aim of this study was therefore to determine if it is possible to establish algae and cyanobacteria on gold mine tailings. Different treatments of Chlamydomonas, Microcoleus and Nostoc were inoculated on gold mine tailings in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Lloyd P. Soil algae and cyanobacteria on gold mine tailings material: Comments on Seiderer et al (2017) They reported the pyrites content as <5%.…”
Section: How To Citementioning
confidence: 99%
See 1 more Smart Citation
“…Lloyd P. Soil algae and cyanobacteria on gold mine tailings material: Comments on Seiderer et al (2017) They reported the pyrites content as <5%.…”
Section: How To Citementioning
confidence: 99%
“…
HOW TO CITE:Lloyd P. Soil algae and cyanobacteria on gold mine tailings material: Comments on Seiderer et al (2017) They reported the pyrites content as <5%.It is known that, under the conditions on tailings dams, pyrites oxidise and generate acid. This process is dynamic; it starts when the soil pH is less than about 5 and continues until most of the pyrite in the upper few metres has oxidised.
…”
mentioning
confidence: 99%
“…The forest and herbaceous ecosystems have different abilities to influence the formation of their internal phytocenotic environment and the composition of the organisms that inhabit them [2][3][4][5]. The various studies have shown the specific features of algal communities in forest, steppe, desert, and other ecosystems [6][7][8][9][10][11]. This is consistent with the definition of the essence of the ecosystem, 1049 (2022) 012072 IOP Publishing doi:10.1088/1755-1315/1049/1/012072 2 where it is represented by a set of interconnected organisms that function in the same territory and interact with the environment in such a way that the flow of energy forms clearly defined biotic structures and the circulation of substances between the living and nonliving components.…”
Section: Introductionmentioning
confidence: 99%
“…Metal solution utilizing For the first set of experiments and screening of the strains, gold pure solution (3.5 ppm) were utilized. For the second set of experiment, Mouteh goldmine soil containing (2 ppm) Au 3+ in 1000 Litter culture medium was used.Inocoulation of cyanobacteria 300 gr soils inoculated with 0.5 gr Phormidium tenue and Oscillatoria tenuis separately(Seiderer et al, 2017). The physico-chemical characteristics of the soil, before and after the inoculation of soil were determined during two weeks.…”
mentioning
confidence: 99%